Metals from cell to environment: Connecting Metallomics with other omics - Vijeta Singhand Kusum Verma (Open Journal of Plant Science - Peertechz Publications, 2018)
Research activities and data collection of metals present in living organisms are called as "metallomics". In metallomics, biomolecules incorporating metal ions viz. metalloenzymes and metalloproteins, are known as "metallomes". Metallomics aims to identify metallomes of living organisms and to annotate the physiological signifi cance as well as the biological functions. However, in order to ascertain metallomics to be the part of biometal science, recent analytical technologies like chemical speciation are required to analyze the metallomes. Environmental applications like bioleaching, phytoremediation of soil by using microbes, and to deal with the uptake, transport, storage of trace metals necessary for protein functions and biomarkers identifi cation under ecotoxicological studies really require metallomics involvement. As an interdisciplinary research area, metallomics cover plant and animal physiology, nutrition and become a potential candidate in pharmacology, biogeochemistry and clinical chemistry. Metallomics uses analytical and spectroscopic methods to fi nd the quantitative and qualitative information about metal ions that are present as ligands a well multifaceted biological matrix in trace amounts or occur as noncovalent complexes in order to perform different biological processes. Latest spectroscopic methods along with in-silico approaches including bioinformatics are the important tools needed for research activities in metallomics. The present review highlights the basics of metallomics in biological sciences and its emergence as a novel omics era in relation to other fi elds. Besides the above aspects, applications and future prospects of metallomics have been highlighted.